KEANEKARAGAMAN JENIS KUPU-KUPU (PAPILIONOIDEA) DI GUNUNG API PURBA NGLANGGERAN [The Diversity of Butterflies (Papilionoidea) at Nglanggeran Ancient Volcano] - Aprilianti, Atilla Nur Melania; Aptari, Zahra; Zabily, Rio; Rahmawati, Yunita Fera (Berita Biologi, 2023)
The presence of butterflies can be found in several types of habitats and can be used as an indicator of environmental conditions. Geologically, the Nglanggeran Ancient Volcano is unique and has high scientific value. It is necessary to update the butterfly diversity data to determine the diversity of butterflies at Nglanggeran Ancient Volcano. The purpose of this study was to determine the diversity, richness, evenness, and dominance of butterfly species at Nglanggeran Ancient Volcano. The exploration method was carried out to obtain data for three repetitions. There were 51 butterfly species with a total of 584 individuals, consisting of Nymphalidae (54.55%), Papilionidae (21.82%), Pieridae (20.00%) and Lycaenidae (3.64%). The index value of butterfly species diversity at Nglanggeran Ancient Volcano (2.97) was medium. The species evenness index (0.83) indicated that the species was relatively stable and evenly distributed. The richness of butterfly species was high, i.e. 6.70, suggesting that the current habitat was suitable for the life of the butterflies. The dominance index value was low, i.e. 0.12, indicating that there was no domination of certain species. The abundant species were Eurema sp. (23.12%), Ideopsis juventa (7.02%), and Catopsilia pomona (6.85%).